2000
DOI: 10.1182/blood.v95.9.2869.009k18_2869_2874
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-16 in delayed-type hypersensitivity reaction

Abstract: Interleukin (IL)-16 is a chemoattractant cytokine for CD4+ leukocytes. Because delayed-type hypersensitivity (DTH) reaction is mediated by T helper 1 (Th1) cells and CD4+ T cells can be chemoattracted by IL-16, we have investigated the involvement of IL-16 in the DTH reaction. Immunohistochemical analysis revealed the IL-16 expression in infiltrating cells and epithelial cells in the DTH footpads. The IL-16 expression was also detected intracellularly in the infiltrating cells. In addition, markedly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 39 publications
2
16
0
1
Order By: Relevance
“…Among other effectors function, macrophages are important to mediate antigen clearance at the site of inflammation and initiate tissue regeneration [24,25]. Our findings demonstrated that high-dose EtOH administration has a drastic impact in imumunogen-driven DTH, reported as impaired OVA clearance in vivo after Figure 3 Long-term impact of high-dose ethanol (EtOH) administration on peritoneal macrophage functional aspects.…”
Section: Discussionsupporting
confidence: 93%
“…Among other effectors function, macrophages are important to mediate antigen clearance at the site of inflammation and initiate tissue regeneration [24,25]. Our findings demonstrated that high-dose EtOH administration has a drastic impact in imumunogen-driven DTH, reported as impaired OVA clearance in vivo after Figure 3 Long-term impact of high-dose ethanol (EtOH) administration on peritoneal macrophage functional aspects.…”
Section: Discussionsupporting
confidence: 93%
“…Some data suggest a role for IL‐16 in the pathogenesis of ILDs. This cytokine, which is involved in the pathogenesis of hypersensitivity reactions ( 101), might direct lymphocyte migration from the circulation into sites of inflammation and tissue injury in ILDs. In fact, IL‐16 shares chemoattractant activity for eosino‐phils and CD4 T cells, and high amounts of IL‐16 have been detected in ILDs, specifically at sites of inflammatory processes, where a perivascular accumu‐lation of lymphocytes may be demonstrated ( 102).…”
Section: The Cytokine Network In Ildsmentioning
confidence: 99%
“…Many studies have shown that the increasing expression of IL-16 has been demonstrated in a variety of diseases, including asthma. 30 Interleukin-16 was previously identified in the BALF 4 hr after antigen challenge in asthmatic subjects. 31 Increased airway expression of IL-16 was detected in bronchial biopsy samples obtained from allergic subjects with asthma 24 hr after allergen challenge.…”
Section: Discussionmentioning
confidence: 99%